2016
DOI: 10.1371/journal.pone.0164193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of TORC1 Inhibition during the Early and Established Phases of Polycystic Kidney Disease

Abstract: The disease-modifying effects of target of rapamycin complex 1 (TORC1) inhibitors during different stages of polycystic kidney disease (PKD) are not well defined. In this study, male Lewis Polycystic Kidney Disease (LPK) rats (a genetic ortholog of human NPHP9, phenotypically characterised by diffuse distal nephron cystic growth) and Lewis controls received either vehicle (V) or sirolimus (S, 0.2 mg/kg by intraperitoneal injection 5 days per week) during the early (postnatal weeks 3 to 10) or late stages of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 80 publications
(125 reference statements)
2
19
0
Order By: Relevance
“…Studies have shown that renal ischemia for more than 20 min will cause damage, ischemia for 20–40 min is reversible, but reperfusion after ischemia for more than 40 min can cause permanent damage ( 3 ). Studies have shown that the development of tolerance of organs to ischemia can inhibit or reduced the ischemia-reperfusion injury ( 4 ). Takahashi-Sato et al ( 5 ) carried out a study to explore the effects of different preconditioning and postconditioning methods on ischemia/reperfusion in the heart.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that renal ischemia for more than 20 min will cause damage, ischemia for 20–40 min is reversible, but reperfusion after ischemia for more than 40 min can cause permanent damage ( 3 ). Studies have shown that the development of tolerance of organs to ischemia can inhibit or reduced the ischemia-reperfusion injury ( 4 ). Takahashi-Sato et al ( 5 ) carried out a study to explore the effects of different preconditioning and postconditioning methods on ischemia/reperfusion in the heart.…”
Section: Introductionmentioning
confidence: 99%
“…In PKD, expansion of fluid-filled cysts drives an increase in total kidney volume (TKV) [5]. A number of studies [13][14][15] have shown that increasing TKV corresponds to a more rapid decline in renal dysfunction. Measurement of the cystic index (i.e., the ratio of cystic area or cystic volume to renal parenchymal area or TKV, respectively) is critical to inform of disease progression [5].…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the cystic index (i.e., the ratio of cystic area or cystic volume to renal parenchymal area or TKV, respectively) is critical to inform of disease progression [5]. Furthermore, at least in preclinical PKD models, the efficacy of a number of therapeutic strategies is determined by the ability of these regimens to retard the progressive increase in cystic index [13][14][15]. Measurement of the cystic area and time-dependent changes therein is therefore critical to inform of both disease status and drug efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…13 To our knowledge the longitudinal changes in angiogenesis and peritubular capillary loss, and their relationship to cyst formation have not been evaluated in experimental models of PKD. Furthermore, in previous studies we and others have shown the mammalian target of rapamycin (mTOR) inhibitor, sirolimus attenuates kidney cyst growth in experimental PKD, 14,15 but experimental studies in liver and colon cancer suggest that it also has anti-angiogenic properties. 16,17 Therefore, the aim of this study was to test the following hypotheses: (i) angiogenesis is coupled with kidney cyst expansion, and the loss of peritubular capillary networks which precedes the onset of interstitial fibrosis; and (ii) sirolimus reduces angiogenesis in PKD.…”
Section: Introductionmentioning
confidence: 99%